Vocational education and training in Denmark : short description - (:unkn) unknown (Publications Office of the European Union, 2012)
This overview of vocational education and training (VET) in Denmark is published during the seventh Danish Presidency of the Council of the EU (first half of 2012). It forms part of the series of short descriptions regularly published by Cedefop on national VET systems. "Reflecting on national education and training priorities, and recent developments in the system, priority has been given to the link between education and training and employment, in particular by developing a benchmark for employability and a recommendation on recognition of informal and non-formal learning. The ultimate goal is to ensure flexibility and responsiveness to labour market needs in education and training and to provide a strong framework for lifelong learning." (Hrsg., BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungssteuerung; Bildungsfinanzierung; Bildungspersonal; Berufsberatung; Dänemark